Enhancing Conceptual Understanding through Cooperative Learning: The Make a Match Approach with Doremi Media in Education - Ranti Afriani; Erianjoni; Dary Nasmi Fauziah (International Journal of Elementary Education, 2026)
The study addresses the issue of low student participation and conceptual understanding in learning environments, impacting overall educational outcomes. This research aims to improve these aspects through the implementation of a Cooperative Learning model, specifically the Make A Match technique, using Doremi media. This Classroom Action Research (CAR) was conducted in two cycles with fourth-grade students comprising 10 participants. Data were collected through observations, tests, and questionnaires. Both qualitative and quantitative data analysis techniques were employed. The findings revealed a significant increase in student participation during the implementation of the Make A Match model with Doremi media. Participation data showed consistent improvement from Cycle I to Cycle II. Additionally, there was a notable enhancement in students' conceptual understanding post-intervention, as evidenced by increased average test scores from before to after the intervention. The data analysis indicated a positive relationship between student participation in cooperative learning and their conceptual understanding, with more actively engaged students tending to demonstrate better comprehension. Furthermore, the trend in students’ conceptual understanding showed steady growth throughout the learning period.The practical implication of this study is that the Make A Match model with Doremi media can serve as an effective strategy for enhancing student participation and conceptual understanding in Sociology education.